2020
DOI: 10.1111/jth.14830
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of venous thromboembolism in patients with severe novel coronavirus pneumonia

Abstract: Background Three months ago, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) broke out in Wuhan, China, and spread rapidly around the world. Severe novel coronavirus pneumonia (NCP) patients have abnormal blood coagulation function, but their venous thromboembolism (VTE) prevalence is still rarely mentioned. Objectives To determine the incidence of VTE in patients with severe NCP. Methods In this study, 81 severe NCP patients in the intensive care unit (ICU) of Union Hospital (Wuhan, China) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

76
1,817
14
127

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,706 publications
(2,079 citation statements)
references
References 15 publications
76
1,817
14
127
Order By: Relevance
“…Another aspect that needs to be highlighted is the increased CVD risk in patients with COVID-19. The prevalence of venous thromboembolism (VTE) in these patients has been reported as 25% and VTE is associated with an unfavorable prognosis [19]. Anticoagulant therapy, mainly with low molecular weight heparin, appears to be associated with a better prognosis in severe COVID-19 patients who have sepsis-induced coagulopathy criteria or markedly elevated D-dimer levels [20].…”
Section: Abstract: Sars-cov2; Covid-19; Ace2: Venous Thromboembolism;mentioning
confidence: 99%
“…Another aspect that needs to be highlighted is the increased CVD risk in patients with COVID-19. The prevalence of venous thromboembolism (VTE) in these patients has been reported as 25% and VTE is associated with an unfavorable prognosis [19]. Anticoagulant therapy, mainly with low molecular weight heparin, appears to be associated with a better prognosis in severe COVID-19 patients who have sepsis-induced coagulopathy criteria or markedly elevated D-dimer levels [20].…”
Section: Abstract: Sars-cov2; Covid-19; Ace2: Venous Thromboembolism;mentioning
confidence: 99%
“…We defi ned a D-dimer at least 6 times the upper limit of normal (3,000 ng/mL fi brinogen equivalent units [FEU]) as the threshold value to defi ne high-risk patients. 5,10 There are currently no data to guide how to address a hypercoagulable pattern on viscoelastic testing (thromboelastography or rotational thromboelastometry). In line with current guidance from the American Society of Hematology (ASH) and the ISTH, we do not routinely use viscoelastic testing to assess hypercoagulability.…”
Section: ■ Laboratory Testingmentioning
confidence: 99%
“…Two recent studies support this clinical impression, reporting a deep vein thrombosis (DVT) rate of 25% 5 and cumulative incidence rates of DVT, pulmonary embolism, and arterial thrombosis of 31% 4 ; and 81% of events reported by Klok et al were pulmonary thromboemboli. 4 In Cleveland Clinic ICUs, we are fi nding that point-of-care ultrasonography (POCUS) detects similar rates of DVT (estimated 25% to 30%) and frequent fi ndings of "slow venous fl ow."…”
mentioning
confidence: 90%
“…In 2 retrospective studies, venous thromboembolism was diagnosed in about 1 in 4 patients admitted to the intensive care unit with COVID-19. 4,5 In 1 study, this occurred despite thromboprophylaxis with low-molecularweight heparin. 5 Available studies have not reported bleeding as a common complication, although the literature is evolving rapidly.…”
Section: Covid-19-associated Coagulopathy Appears To Be Prothromboticmentioning
confidence: 99%